2016
DOI: 10.1186/s12986-016-0108-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic over-nutrition and dysregulation of GSK3 in diseases

Abstract: Loss of cellular response to hormonal regulation in maintaining metabolic homeostasis is common in the process of aging. Chronic over-nutrition may render cells insensitive to such a hormonal regulation owing to overstimulation of certain signaling pathways, thus accelerating aging and causing diseases. The glycogen synthase kinase 3 (GSK3) plays a pivotal role in relaying various extracellular and intracellular regulatory signals critical to cell growth, survival, regeneration, or death. The main signaling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 225 publications
(316 reference statements)
0
28
0
Order By: Relevance
“…Glycogen synthase kinase 3 (GSK3) is a family of serine/threonine kinases comprising GSK3α and GSK3β which was originally identified as a key controller of metabolism via its inhibitory phosphorylation of glycogen synthase [1]. More recently, GSK3 has been shown to control a broad range of cellular functions through phosphorylation of many target proteins [2]. These functions include cell-cycle progression, energy homeostasis and inflammation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Glycogen synthase kinase 3 (GSK3) is a family of serine/threonine kinases comprising GSK3α and GSK3β which was originally identified as a key controller of metabolism via its inhibitory phosphorylation of glycogen synthase [1]. More recently, GSK3 has been shown to control a broad range of cellular functions through phosphorylation of many target proteins [2]. These functions include cell-cycle progression, energy homeostasis and inflammation [2].…”
Section: Introductionmentioning
confidence: 99%
“…GSK is constitutively active and is inhibited either by Ser-9 phosphorylation or protein-binding sequestration (43,44). It has been shown that GSK3B activity can be regulated by scaffolds like AKAP220 (45).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of recent experimental observation that elevated IL-17RC expression was present in peripheral blood samples of AMD patients [ 6 ] and that overexpression of IL-17RC in transfected RPE or monocytes was associated with uncontrolled GSK3 activation [ 8 ] , we postulated that the etiology of AMD might be related to overstimulation-induced-insensitivity of the PI3K/Akt/GSK3 pathway and uncontrolled (or released) GSK3 activity [ 15 ] . To test this hypothesis, we examined the phosphorylation status of PI3K, Akt, and GSK3, as well as that of GSK3 substrates in PBMC of AMD patients.…”
Section: Discussionmentioning
confidence: 99%